HPV vaccination of gay, bisexual and other men who have sex with men in sexual health and HIV clinics in England: vaccination uptake and attendances during the pilot phase. (26th April 2019) - Checchi, Marta; Mesher, David; McCall, Mark; Coukan, Flavien; Chau, Cuong; Mohammed, Hamish; Duffell, Stephen; Edelstein, Michael; Yarwood, Joanne; Soldan, Kate
Abstract : Background: Human papillomavirus (HPV) vaccination for gay, bisexual and other men who have sex with men (GBMSM) aged up to 45 years attending sexual health clinics (SHC) and HIV clinics began in England as a pilot in June 2016, with national roll-out from April 2018. The recommended course is three doses of the quadrivalent HPV vaccine over one to 2 years. We present the methodology and results of monitoring vaccination uptake (initiation and completion), and attendance patterns, during the pilot phase. Methods: Total numbers of eligible GBMSM receiving HPV vaccine doses were extracted from routine datasets from pilot start to end of March 2018. Numbers of attendances since January 2009 were extracted and tested for trends before and after introduction of HPV vaccination. Results: Overall, first dose uptake was 49.1 % (23 619/48 095), with clinics with highest data completeness achieving close to 90% uptake during the pilot period. Refusals were very low (3.5%). There was no evidence of increases in the number of GBMSM attendances at pilot SHC. Conclusions: HPV vaccination has not caused important deviations to expected attendance patterns of GBMSM at SHC throughout the pilot phase. Overall, recorded initiation has been encouraging given known issues with data recording, as is current status of second and third dose completion. Attendances, vaccination initiation and completion will continue to be monitored alongside surveillance of anogenital warts diagnoses and of rectal HPV prevalence.